2015
DOI: 10.15376/biores.10.4.7302-7314
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kenaf Loading on Processability and Properties of Linear Low-Density Polyethylene/Poly (Vinyl Alcohol)/Kenaf Composites

Abstract: aThis study was conducted to evaluate the possibility of utilizing kenaf (KNF) in LLDPE/PVOH to develop a new thermoplastic composite. The effect of KNF loading on the processability and mechanical, thermal and water absorption properties of linear low-density polyethylene/poly (vinyl alcohol)/kenaf (LLDPE/PVOH/KNF) composites were investigated. Composites with different KNF loadings (0, 10, 20, 30, and 40 phr) were prepared using a Thermo Haake Polydrive internal mixer at a temperature of 150 °C and rotor spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…The stabilization torque is the equilibrium torque value that was recorded at the end of the mixing, i.e., at the end of 10 min. The stabilization torque increased for both composites as the KNF loading increased, which suggested that the processing of the composites is easier at lower KNF loadings (Pang et al 2015). However, at similar KNF loadings, composites with TMS exhibited higher stabilization torque values compared with the control composites.…”
Section: Processing Torquementioning
confidence: 92%
See 1 more Smart Citation
“…The stabilization torque is the equilibrium torque value that was recorded at the end of the mixing, i.e., at the end of 10 min. The stabilization torque increased for both composites as the KNF loading increased, which suggested that the processing of the composites is easier at lower KNF loadings (Pang et al 2015). However, at similar KNF loadings, composites with TMS exhibited higher stabilization torque values compared with the control composites.…”
Section: Processing Torquementioning
confidence: 92%
“…16). The three steps of thermal degradation involved: i) evaporation of absorbed moisture on the surface of the composites at 100 °C (Pang et al 2015), ii) decomposition of hemicelluloses, cellulose, and lignin at 200 to 400 °C (Fisher et al 2002;Chun et al 2013), and iii) decomposition of the LLDPE/PVA matrix at 450 to 550 °C. Table 2 shows the TGA parameters of control and TMS-treated LLDPE/PVA/KNF composites.…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%
“…Therefore, the thermal stability of the composites increases with the sugar palm loading increase. 45 …”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…The presence of the sugar palm yarn restricts the unsaturated polyester matrix from moving freely, thereby increasing the rigidity of the composite. 45 The elongation at break of sugar palm fibre yarn reinforced unsaturated polyester composites with different fibre loadings are also affected. The elongation at break for composites at 50 wt% is the highest as compared to 10, 20, 30 and 40 wt% of fibre loadings.…”
mentioning
confidence: 99%
“…Natural fibers such as kenaf (KNF), wood, jute, hemp and bagasse have become an ideal choice as biodegradable materials to blend with thermoplastics and utilized in different applications (Balaji et al 2014;Husseinsyah et al 2016;Pang et al 2015). KNF based polymer composites are being increasingly used in automotive parts such as car door panels, seat back board and door trim due to their light weight, low cost and environmental friendly (Kamal et al 2014;Pai & Jagtap 2015).…”
Section: Introductionmentioning
confidence: 99%